Age-dependent VDR peak DNA methylation as a mechanism for latitude-dependent multiple sclerosis risk - Lawrence T. C. Ong (Epigenetics & Chromatin, 2021)
Abstract Background The mechanisms linking UV radiation and vitamin D exposure to the risk of acquiring the latitude and critical period-dependent autoimmune disease, multiple sclerosis, is unclear. We examined the effect of vitamin D on DNA methylation and DNA methylation at vitamin D receptor binding sites in adult and paediatric myeloid cells. This was accomplished through differentiating CD34+ haematopoietic progenitors into CD14+ mononuclear phagocytes, in the presence and absence of calcitriol. Results Few DNA methylation changes occurred in cells treated with calcitriol. However, several VDR-binding sites demonstrated increased DNA methylation in cells of adult origin when compared to cells of paediatric origin. This phenomenon was not observed at other transcription factor binding sites. Genes associated with these sites were enriched for intracellular signalling and cell activation pathways involved in myeloid cell differentiation and adaptive immune system regulation. Conclusion These results suggest vitamin D exposure at critical periods during development may contribute to latitude-related differences in autoimmune disease incidence.